2000
DOI: 10.1348/014466500163220
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental bonding and core beliefs in anorexic and bulimic women

Abstract: Longitudinal research is needed to confirm these findings among anorexic and bulimic women. Clinically, these findings provide insight into the possible origins or core beliefs, and hence might aid their challenge in schema-focused cognitive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 18 publications
9
61
2
Order By: Relevance
“…In other words, behavioral strategies are used to reduce awareness of negative emotions. These findings are implicitly in agreement with the previous literature indicating that women with eating disorders scored higher on early maladaptive schemas than non-clinical women using self report measures (10)(11)(12)(13)(14)(16)(17)(18). In addition, the present results are in line with previous experimental researches reporting that the subliminal activation of abandonment schema increased the amount of food eaten in non-clinical women (27,29,(42)(43)(44).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, behavioral strategies are used to reduce awareness of negative emotions. These findings are implicitly in agreement with the previous literature indicating that women with eating disorders scored higher on early maladaptive schemas than non-clinical women using self report measures (10)(11)(12)(13)(14)(16)(17)(18). In addition, the present results are in line with previous experimental researches reporting that the subliminal activation of abandonment schema increased the amount of food eaten in non-clinical women (27,29,(42)(43)(44).…”
Section: Discussionsupporting
confidence: 93%
“…It proposes that all types of patients with eating disorders score higher on maladaptive schemas such as abandonment, emotional deprivation, and defectiveness/shame (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, the theory postulated that patterns of schema processes (overcompensation or avoidance strategy) explain the differences between restrictive and bulimic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies provide support for the theory that core beliefs are related to parenting experiences, and that different experiences with maternal and paternal figures may be important in the determination of core belief outcome (Harris & Curtin, 2002;Leung, Thomas, & Waller, 2000;Shah & Waller, 2000). Furthermore, Cecero, Nelson and Gillie (2004) demonstrated that abandonment beliefs predicted a preoccupied romantic attachment style, a dismissing style was predicted by social isolation, emotional deprivation, abandonment and subjugation beliefs, and a fearful style was predicted by mistrust/abuse and emotional inhibition beliefs.…”
Section: Theoretical Proposals For a Link Between Representations Of mentioning
confidence: 99%
“…18 They are associated with both Axis II personality disorders and Axis I symptomology including anxiety, depression, 19 eating disorders, 20 obsessive-compulsiveness, hostility, phobic anxiety, and psychoticism. 21 Unhealthy beliefs have also been associated with poor parental bonding 22,23 and with representations of current attachment relationships, [24][25][26] which lends credence to their theorized origins, and also indicates the potential for unhealthy beliefs to influence an individual's own parenting styles and practices. 17 The group of beliefs that cluster under the domain of ''disconnection and rejection,'' including abandonment, mistrust/abuse, emotional deprivation, defectiveness/shame, and social isolation, have been proposed to be the most damaging and unconditional group of beliefs, which develop most early in childhood, 27 and it is this group of beliefs that appear to show most consistent relationships with attachment and interpersonal styles.…”
Section: Introductionmentioning
confidence: 87%